Contribución al conocimiento ficológico y calidad de agua de la laguna La Arocena (pcia. de La Pampa, Argentina) - Bazán, Graciela Inés (2012)
This work is part of an overall project that includes the study of the dynamics of algae in aquatic ecosystems in the province of La Pampa (Argentina). The aim of this contribution is to cite the species recorded for the Arocena and determine the saprobic and water quality of the lake. From October 2006 to August 2007 these were seasonal sampled in the Arocena shallow lake (Maracó Department), La Pampa. The samples were collected at six prefixed sites with phytoplankton net opening of 25 microns mesh. The physico-chemical variables (T °C, pH, conductivity, nitrites, nitrates, dissolved oxygen, among others) were obtained using portable sensors and subsequent laboratory techniques. These parameters provided an autecological characterization of the species studied and some of them extended the range of tolerance to the literature. Of all the species listed (251), 40% were Chlorophyceae, 32% Bacillariophyceae, 22% Cyanophyceae, Euglenophyceae 3.5% and 2.5% remaining Chrysophyceae, Xanthophyceae, Cryptophyceae and Dinophyceae. The determined state was β mesosaprobic and the water quality was α mesosaprobic.